2023
DOI: 10.1002/nop2.1763
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between moral sensitivity of nurses and quality of nursing care for patients with COVID‐19

Abstract: Aim: This study aimed to: (1) assess the level of moral sensitivity of nurses and the quality of nursing care for patients with COVID-19 in Iran; and (2) identify the relationship between the moral sensitivity of nurses and the quality of nursing care for patients with COVID-19 in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…When examining nurses' moral sensitivity, studies have reported varying results. Two studies from Iran reported that most nurses had moderate moral sensitivity [ 24 , 25 ]. Filipova (2009) found that nurses working in one of the Midwestern state of the US had low moral sensitivity [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…When examining nurses' moral sensitivity, studies have reported varying results. Two studies from Iran reported that most nurses had moderate moral sensitivity [ 24 , 25 ]. Filipova (2009) found that nurses working in one of the Midwestern state of the US had low moral sensitivity [ 26 ].…”
Section: Introductionmentioning
confidence: 99%